Expanded hemodialysis : innovative clinical approach in dialysis - Ronco, Claudio 1951- (Contributions to nephrology / series editor Claudio Ronco, 2017)
Despite constant significant advances, cardiovascular as well as more general outcomes of hemodialysis treatment remain unsatisfactory. The introduction of innovative 'high retention onset' membranes has led to the development of a new treatment modality called 'expanded hemodialysis' (HDx), which is the focus of this book. This new therapy is likely to benefit end-stage kidney disease patients, thanks to enhanced removal of molecules retained by current dialysis techniques. HDx is simple to set up and application does not require special hardware or specific nursing skills. This book contains emerging evidence and fascinating new hypotheses on HDx. It is highly recommended for all physicians and healthcare professionals who are caring for dialysis patients and are seeking innovation and improved care solutions. It will also be of considerable interest to students and fellows.